Ethyl acetate extract of Citrullus colocynthis (Linn.) Schrad. fruit suppresses angiogenesis - Mayuri Gaikwad; Vaishali Shirsat; Mrunal Bulbule; Samidha Kalekar; Renuka Munshi (GarVal Editorial Ltda., 2019)
Context: Anti-angiogenesis is a targeted therapy that uses drugs or other substances to stop tumors from making new blood vessels. Citrullus colocynthis is a medicinal plant that has anticancer property mediated by apoptosis. Aims: To evaluate the anti-angiogenic potential of C. colocynthis fruits extract through chorioallantoic membrane (CAM) assay. Methods: For the CAM assay, heparin (an anti-angiogenic agent) was used as a positive control, and quercetin (Q) as the marker compound in the extracts to demonstrate the inhibition of angiogenesis. The reduction in the number of blood vessels in each area and in each image was used as a measure to determine the anti-angiogenic activity of the extract. Results: From the results of phytochemical screening, the polyphenol and flavonoid contents of the ethyl acetate extract were 0.6708 mg equivalent of gallic acid per gram of the dry extract and 7.65 mg equivalent of Q per gram of the dry extract, respectively. From the results of CAM assay, Q caused marked reduction in the formation of new blood vessels. Similarly, ethyl acetate extract of C. colocynthis fruits (50 µg/mL) showed 53.52% inhibition of blood vessel formation in the CAM vasculature, whereas 25 µg/mL of Q exhibited 64.78% inhibition. The analysis with Bonferroni's post-hoc test showed statistically significant difference at p<0.0001, with respect to the positive control, heparin. The EC50 values obtained by non-linear regression analysis using GraphPad Prism software 8.1.2 were 14.74 µg/mL (Q) and 44.13 µg/mL (ethyl acetate fruit extract of C. colocynthis). Conclusions: Ethyl acetate extract of C. colocynthis fruits demonstrated potential angiogenesis suppression activity.